Multiple Early-Stage Malignant Melanoma of the Esophagus with a Long Follow-Up Period After Endoscopic Treatment: Report of a Case and a Literature Review - Miyamoto, Shin’ichi; Morita, Shuko; Muto, Manabu (IntechOpen, 2012)
None